P750 Association between the use of antihypertensive agents and disease severity in patients with inflammatory bowel disease. (25th January 2019) - Mantaka, A; Tsoukali, E; Fragaki, M; Karmiris, K; Viazis, N; Mantzaris, G; Koutroubakis, I
Abstract: Background: Accumulating evidence suggests the implication of angiotensin II in the pathogenesis of inflammatory bowel diseases (IBD) via its role as an inflammatory mediator. Recent data highlight beneficial effects of angiotensin II receptor blockers (ARBs) in experimental colitis as a result of regulation of mechanisms of colonic inflammation, oxidative stress and apoptosis. The aim of the present study was to evaluate the prevalence of hypertension among Greek IBD patients and the possible impact of the use of anti-hypertensive medications on the IBD course. Methods: This is a retrospective analysis of prospectively collected data from 425 consecutive IBD patients [251 males, 223 Crohn's disease (CD), age range 30–89 years, mean (±SD) age at diagnosis 41.6 ± 16.1 years and mean follow-up of 12.5 ± 9.1 years] derived from the IBD registries of 3 participating IBD referral Centres. The presence of hypertension and the use of anti-hypertensive agents were recorded in all patients. Clinical characteristics and IBD severity were compared between IBD patients with hypertension and age- and sex-matched IBD patients without concurrent hypertension. Results: The prevalence of hypertension was calculated at 29.9% in Greek IBD patients. Among 127 IBD patients with concurrent use of anti-hypertensive drugs, 50 were on ARBs, 35 on angiotensin converting enzyme inhibitors and 39 on b-blockers or calcium-channel blockers. IBD patients on anti-hypertensives were found to use less frequently anti-TNFα ( p < 0.001) or immunomodulators ( p = 0.001), as well as to have lower rates of hospitalisation for relapse ( p < 0.001) and a tendency for lower rates of IBD-related surgery ( p = 0.061) compared with patients without any use of anti-hypertensives. After multi-variate adjustment for gender, BMI, smoking history and IBD type, the use of anti-hypertensives remained significantly associated with mild disease as indicated by the absence of all the above parameters: anti-TNF-α or immunomodulator use, IBD-related surgery and >3 hospitalisations for relapse ( p = 0.004). The use of ΑRBs was less frequently correlated with L2 CD ( p = 0.012), anti-TNF-α ( p < 0.001) or immunomodulators' use ( p < 0.001) and with IBD-related hospitalisations ( p = 0.002) compared with other classes of anti-hypertensive drugs. Conclusions: The prevalence of hypertension in Greek IBD patients is 29.9%. The use of antihypertensive agents seems to be independently associated with mild disease. This association is stronger with the use of ΑRBs. Data from larger prospective studies are essential to further evaluate this finding.